A New Method of Predicting Final Mandibular Length Based on the Morphology of Cervical Vertebrae - Manami Yamaguchi; Yong-Il Kim; Heetae Park; Tetsutaro Yamaguchi (Diagnostics)
Background/Objectives: Methods for predicting final mandibular length have been studied for many years. We aimed to estimate the final mandibular length at the end of the growth period by analyzing changes in cervical vertebral morphology using longitudinal lateral cephalograms. Methods: Longitudinal lateral cephalograms of elementary school students aged 6–15 who did not undergo orthodontic treatment, collected between 1965 and 1973, were used. For this analysis, 370 images from 44 female individuals were selected, and cervical vertebral morphology was assessed using the semi-landmark method. Generalized Procrustes analysis and principal component analysis were performed, and changes in maxillofacial skeletal and cervical vertebral morphology were analyzed using a linear mixed model with repeated measures. A predictive formula for estimating final mandibular length was developed based on morphological changes in the fourth cervical vertebra. Results: The difference between the predicted and actual final mandibular lengths using the semi-landmark method was 0.17 ± 0.08 mm. The marginal R2 value of the prediction formula was 0.957, and the conditional R2 was 0.990, demonstrating very high accuracy. The annual increase in mandibular length remained consistent each year but slowed after 14 years of age. Geometric morphometric analysis revealed significant morphological changes in the fourth cervical vertebra at 14 years of age, coinciding with a deceleration in mandibular growth. Conclusions: A highly accurate formula was developed to predict final mandibular length based on morphological changes in the fourth cervical vertebra. Cervical vertebral morphology may provide valuable information related to mandibular growth during adolescence.